2002
DOI: 10.1007/s00420-001-0298-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neck-shoulder and wrist-hand symptoms in a 5-year follow-up study of 3,990 employees in Denmark

Abstract: The results confirm that physical exposures at work influence the development of musculoskeletal symptoms in the neck-shoulder and wrist-hand regions. However, the results also suggest that a psychosocial exposure (social support) and perceived stress symptoms influence musculoskeletal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 30 publications
6
69
1
3
Order By: Relevance
“…Most previous studies demonstrating the link between psychosocial factors and musculoskeletal symptoms originated in Western countries 4,10,12) . Recent studies investigating the relationship between p s y c h o s o c i a l f a c t o r s a n d t h e p r e v a l e n c e o f musculoskeletal symptoms in Thai office workers support this notion 28,29) .…”
Section: Psychosocial Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies demonstrating the link between psychosocial factors and musculoskeletal symptoms originated in Western countries 4,10,12) . Recent studies investigating the relationship between p s y c h o s o c i a l f a c t o r s a n d t h e p r e v a l e n c e o f musculoskeletal symptoms in Thai office workers support this notion 28,29) .…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Ankle/foot symptoms (35%) were the most frequently affected body region followed by low back (34%), knees (33%), hips (28%), shoulders (28%), head/neck (26%), upper back (21%), wrists/hands (14%) and elbows (3%) 3) . Salespersons in department stores are at risk of developing musculoskeletal symptoms because they are exposed to various physical and psychosocial factors which are generally attributable to the development of musculoskeletal symptoms [4][5][6][7] . For example, their jobs involve prolonged standing and they are frequently exposed to manual handling tasks, such as lifting, carrying, pushing and pulling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies (41,42) were excluded because they did not report musculoskeletal complaints for a specific region. Finally, four studies (43)(44)(45)(46) that met all the inclusion criteria and presented their data in a usable way could not be used in the analysis because they did not report findings in respect to any of the predetermined risk factors. Therefore, 14 studies (47-60) on back complaints, 9 studies (58-66) on neck-shoulder complaints, 4 studies (65-68) on hand-wrist complaints and 4 studies (69-72) on lower-extremity complaints were used.…”
Section: Selection Of the Literaturementioning
confidence: 99%
“…Several physical risk factors commonly found in the work environment, such as repetitive motion, awkward postures, and forceful exertions, have been found to be consistently positively associated with musculoskeletal disorders of the upper extremities (1,2). While the strongest associations appear to exist when risk factors are present in combination (3,4), epidemiologic studies have reported an independent, positive association between forceful exertions and specific musculoskeletal disorders of the upper extremities, such as carpal tunnel syndrome and epicondylitis (5)(6)(7)(8). Quantitative estimation of the association between exposure to specific levels of forceful exertions and musculoskeletal disorders of the upper extremities is sparse, however, due partly to the use of imprecise self-report or observational exposure assessment techniques (9)(10)(11)(12).…”
mentioning
confidence: 99%